Atividade antifúngica de extratos de plantas a Colletotrichum gloeosporioides - Celoto, Mercia Ikarugi Bomfim [UNESP]; Papa, Marli de Fátima Stradioto [UNESP]; do Sacramento, Luis Vitor Silva [UNESP]; Celoto, Fernando Juari [UNESP] (My University, 2008)
The present work aimed to evaluate the effect fungitoxic of plant extracts on the mycelial growth and on the spores germination of C. gloeosporioides. The plant extracts were obtained starting from dried ground plants, using water and ethilic alcohol as extractor. Twenty-two plant species were used to obtain the extracts. The extracts were tested by means of the incorporation of 20% (v/v) in PDA medium, before or after sterilization. The percentage of inhibition of the mycelial growth (PIM) was determined. Extract in the proportion of 50% was added to a spore suspension used to determine the percentage of inhibition of the spores germination (PIS). The hidroetanolic extracts provided larger PIM of C. gloeosporioides, while larger PIS was obtained with the aqueous extracts. Non autoclaved extracts was the most efficient in mycelial growth of C. gloeosporioides, even more than the autoclaved ones. Aqueous and hidroetanolic extracts of Momordica charantia and hidroetanolic extract of Eucalyptus citriodora provided higher PIM. Aqueous extracts of Luffa acutangula, Eucalyptus citriodora, Chenopodium ambrosioides, and Bauhinia, and hidroetanolic extracts of Ruta graveolens, Eucalyptus citriodora, Zingiber officinale and Chenopodium ambrosioides inhibited more than 90% of spores germination.
Antifungal activity of plant extracts to Colletotrichum gloeosporioides
Keywords: Alternative control; Extracts vegetable; Inhibition of the mycelial growth; Inhibition of the spores germination; Medicinal plants